NEW ELECTORAL TECHNIQUES: WILL UKRAINE ACCEPT THEM? - Яцунська, О.О. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2015)
This study endeavors to analyze the impact of the new media technologies employed during the US presidential election campaigns in 2008 and 2012 on fundraising and contemporary politics, focusing on fundraising schemes utilizing online and mobile applications, the use of which enabled the current President (then a Democratic Party candidate) to raise more funds - for the first time in decades – than the Republicans, by reaching out to a wider audience of Internet users.